SOME SUGGESTIOS ON THE FOLK TRADISIONAL MEDIA THE INDONESIA EXPERINCE. - Kertopati, Ton (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
Â Althouht a product of the cultural heritage is nevertheless notes for its uniqueness were one to try to characterize it in a few words.It might be said to teveal a preference for internal grace as opposed to external splendor. The sense of beauty characteristic of the javanese and sundanese wayang as expressed in such concepts of refined elegance and the pathos of nature, works of aesthetic and emotional harmony.Culture is a general term for such areas as communicating, learning religion and the arts which again an be segmented into several forms of uniquenessNevertheless we may apply such domentaries as the one made to at at easty the wayang as the folk tradisional media.